episodic onset of explosive and silicic-dominated volcanism in a continental rift; insights from the Permian Oslo Rift, Norway - Jack Whattam; Ivar Midtkandal; Dougal Jerram; Sara Callegaro; Henrik Svensen (Volcanica)
The nature of rifting episodes and their associated volcanism mark key stratigraphic events in the evolution of volcano-sedimentary basins. Following the final assemblage of Pangea, the European region was subject to rifting and magmatism during crustal re-equilibration throughout the Permian. The aborted, partially eroded Oslo Rift is an excellent archive of this Permian magmatism, but the late-stage volcanological evolution is poorly understood. We present the first detailed documentation of a succession covering this period, with mafic lavas and volcaniclastic (tuff breccia) deposits, trachy-andesitic tuffs, and rheomorphic to moderately welded ignimbrites. Contrary to previous ideas, we show evidence suggesting the development of Strombolian-type scoria-cones, silicic fissure-fed eruptions, and major periods of rift-wide volcanic quiescence. Our observations highlight episodic silicic volcanism characterised by rapid evolution from high-grade ignimbrites to moderately and poorly welded ignimbrites. We infer rapid emptying of large, shallow silicic reservoirs and frequent source switching is responsible for the observed characteristics.